Emergency cranial computed tomography in the management of acute febrile encephalopathy in children. Issue 6 (1st November 1999) - Nadel, S; Joarder, R; Gibson, M; Stevens, J; Britto, J; Habibi, P; Owens, C
Abstract : OBJECTIVE: Evaluation of the influence of emergency cranial computed tomography on the management of acute febrile encephalopathy in children. METHODS: A retrospective study in children with acute febrile encephalopathy who underwent emergency cranial computed tomography within 12 hours of admission to the paediatric intensive care unit. All scans were evaluated by two independent radiologists. RESULTS: Thirty nine children were included. Fourteen scans were abnormal and two had clinically insignificant incidental findings. Four children with focal neurological signs had scans demonstrating extra-axial collections. None required neurosurgical intervention. Clinically, raised intracranial pressure was present in 10 patients. Only five had cerebral oedema on computed tomography; these five children died. Emergency cranial computed tomography influenced subsequent management in no child without focal neurological signs and in only one child with focal neurology. CONCLUSION: Emergency cranial computed tomography in acute febrile encephalopathy in children without focal neurological signs has little influence on subsequent management. Where cranial computed tomography is thought to be necessary, it should be carried out when the child's clinical condition has been stabilised.